The Effect of Reward toward Students’ Motivation in learning English structure at Kampung Inggris Rafflesia Rejang Lebong - Astin Utari (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
Abstract The aimed of this research was to find out the effect of reward toward students’ motivation in Learning English structure at Kampung Inggris Rafflesia Rejang Lebong. It created in quantitative design as a quasi- experimental research. The population of this research was all senior high school graders (they were three classes) and two classes as the sample, the E1 as control class and E3 as experimental class. The techniques of data collecting were pre-test and post-test and supported by questionnaire. The results were taken from post-test that consist of five aspects, they were total score, highest score, lowest score, mean score, and standard deviation. Based on the final result of the five aspects above, the researchers found that reward gave effect for the students’ motivation in learning English structure. It was also could be seen from the results of questionnaire, they felt enjoy, fun and enthusiasm during the teaching-learning were held.